Improving The Professional Teacher Competence Through Clinical Supervision Based on Multicultural Values in Pesantren - Syamsul Arifin; Sutama Sutama; Sekar Ayu Aryani; Harun Joko Prayitno; Waston Waston (Nazhruna: Jurnal Pendidikan Islam, 2023)
This study examines how clinical supervision activities can promote multiculturalism in Indonesia and enhance teacher professionalism. Multicultural education is based on five criteria integrated into clinical supervision activities to improve teacher competence. The goal is to apply multicultural values to education and enhance teacher competency in various areas, such as pedagogy, personality, social skills, and professionalism. The study focuses specifically on two Islamic boarding schools in Ponorogo, East Java, Indonesia. This study uses a qualitative approach for detailed, comprehensive, and in-depth data collection techniques in observation, documentation, interviews, and focused discussions. Based on the findings of the clinical supervision description data through the planning stage, clinical supervision stage, evaluation stage, and follow-up, data analysis techniques using Miles and Huberman are applied, which include data mining, data reduction, data presentation, and conclusion. The study found that clinical supervision activities for teachers in Islamic boarding schools start with planning supervision, followed by microteaching and observation activities to assess teacher learning standards. The development of teacher competency is based on teacher learning preparation, discussions, the teacher as the supervisor of an Islamic boarding school, and the teacher as the main actor in clinical supervision activities. This research highlights the importance of clinical supervision based on multicultural values, as it can enhance pedagogic, personality, social, and professional competencies.